Electrophoretic Fractionation and Characterization of Humic Acids of the Soils of Doon Valley under Sal (Shorea robusta) - Grosh, R. C.; Singhal, R. M.; Sharma, S. D. (Indian Forester, 1980)
Soil humic acids from six soil profiles of the sal forest were fractionated by paper electrophoresis. Results obtained indicate some differences in the degree of polymerisation of the various humic materials between as well as within the Profiles which explains the difference in soil fertility.